ANALISIS PENGARUH KESEMPATAN KERJA, BELANJA BANTUAN SOSIAL DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI PROVINSI KALIMANTAN SELATAN - NURANIAH NURAINAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to see employment opportunities, social assistance spending and economic growth related to poverty in the province of  Sout Kalimantan Province. The data used is time series in the period 2007-2017, using multiple linier regression analysis. The results of the study are partially employment opportunity variables, social assistance spending and growth affect poverty, while simultaneously employment opportunity variables do not affect poverty but social assistance spending and growth variables affect poverty in South Kalimantan Province.Keywords : Poverty, Job Opportunities, Social Assistance Expenditure, Economic Growth.